Sodium Intake and Salt Taste Preference During Adolescence: Followup of a Randomized Controlled Field Trial. (14th June 2022) - Baratto, Paola; Valmorbida, Julia; Sangalli, Caroline; Leffa, Paula; Rauber, Fernanda; Mennella, Julie; Vitolo, Marcia
Abstract: Objectives: Determine whether dietary counseling on breastfeeding and healthy eating for mothers during the early postpartum period interacted with or was independent of sodium intake and pubertal development in predicting the concentration of salty taste most preferred by adolescents. Methods: We conducted follow-up assessments of children aged 12 years (n = 202) whose mothers participated in a randomized controlled field trial when they were infants; the trial was designed to determine the impact of the dietary counseling for low-income mothers during the early postpartum period. Sodium intake was assessed using two, 24-hour dietary recalls from which we focused on sodium from processed and ultra-processed foods, classified according to the "NOVA" system; the most preferred level of salt was evaluated by the Monell two-series, forced-choice, paired comparison tracking method; and pubertal development was classified according to the Tanner stages. The associations of the randomization group, tanner stage, and sodium intake from processed and ultra-processed foods (4 th quartile vs 1 st –3 rd quartiles) with the most preferred level of salt were assessed using multivariate linear regression. Variables such as birth weight, duration of exclusive breastfeeding, household income, skin color, BM-for-age Z, and height-for-age Z score were also included in the multivariate model for adjustment. Results: Independent of randomized groups (p = 0.14), children in Tanner stages 1–3 most preferred significantly higher concentrations of salty taste than those in later stages (β = 0.43; p = 0.02). Higher intakes of sodium from processed and ultra-processed foods were also associated with a preference for higher concentrations of salty taste (β = 0.52; p = 0.01). Conclusions: Prior to the cessation of puberty children most prefer higher concentration of salty of puberty adolescents prefer higher salt concentrations, evidencing that biological needs play an important role in driving salty-taste preferences. Therefore, it is relevant to promote healthy food habits among adolescents to prevent the excessive consumption of processed and ultra-processed foods which are not only rich in sodium, but also in sugar and fat. Funding Sources: Brazil National Council for Scientific and Technological Development; NIH Grant R01DC016616 to JAM.